Poverty and the government in America a historical encyclopedia - Sreenivasan, Jyotsna (Santa Barbara, California ABC-CLIO, 2009)
Covers the U.S. government's responses to poverty from the colonial era to the present day.
v. 1. A-J -- v. 2. K-Z.
Keywords: Poverty -- Government policy -- United States -- Encyclopedias; Public welfare -- United States -- Encyclopedias; Electronic books